A Review on Physical and Rheological Properties of Nano Zinc Oxide Modified Asphalt Mixture - Hamid, Nor Faten Allia; Mohd Yunus, Khairul Nizam (Recent Trends in Civil Engineering and Built Environment, 2023)
In road construction the selection of mixed materials is important. Therefore, use of additives on asphalt as a modification material has been introduced since past year. Rutting is one of the failure factors of the pavement. There are several factors should be in this problem such as traffic loads and weather. But the main effect of this problem is because of aggregate movement and weak asphalt binders. The purpose of this study was to evaluate the performance characteristics for rutting reacting with nano-ZnO as a mixed material in asphalt. Thus, the objective of this study is to find the optimum percentage of nano-ZnO as modified in asphalt binder and to show the effects of nano-ZnO size in rutting resistance of asphalt. In this research, were focus for a result from previous study regarding the suitable percentage to sort up. This case study conduct with gradation of aggregate with AC14 of marshal mix design test and conventional test such as penetration test and softening point test. For sort up the result were extract data from previous study regarding the performance of nano-ZnO with asphalt binder. Then, the result will be compared between the previous study. Based on the result, when the penetration is decrease, the softening point of bitumen is increase. In conclusion, the results show that the addition of ZnO particles can improve the anti-rutting factors of this asphalts, and that the reduction in ZnO particle size has significant positive impacts on the anti-rutting factor of asphalt